ANALISIS KELAYAKAN DESA PENERIMA ZAKAT PRODUKTIF BERDASARKAN MULTI STAGE WEIGH INDEX - Tri Wahyuningsih; Arivatu Rahmatika; Ashlihah - (JoEMS (Journal of Education and Management Studies), 2020)
Cupak Village is one of the villages located in Ngusi Subdistrict, Jombang Regency which has natural potential and good agricultural products but is still an underdeveloped village, so researchers are interested in analyzing empowerment strategies in productive zakat management by using the Village Zakat Index calculation. This research is a descriptive research. The approach used is a quantitative approach. The data is collected by direct survey, as well as interviews obtained from informants who understand the condition of Cupak Village, then the data is processed by a calculation called the Multi-Stage Weigh Index by calculating the results of the five components of the village zakat index, namely the economic, health, education, preaching as well as social and humanitarian. The results of this study indicate the village zakat index value is 0.15 which means that the condition of the Cupak Village is not good and is very prioritized for assistance.